Compensation, Leadership, and Work Discipline: Influences on Employee Performance: Kompensasi, Kepemimpinan, dan Disiplin Kerja: Pengaruh Terhadap Kinerja Karyawan. - Ronald Firdaus; Sumartik (Academia Open, 2024)
This study investigates the impact of compensation and leadership on employee performance, with work discipline serving as an intervening variable. Using a saturated sample of 37 employees at an undisclosed organization, the research employs Partial Least Square analysis. The findings reveal that compensation and leadership both significantly influence work discipline and employee performance. Moreover, work discipline significantly affects employee performance. Notably, leadership exerts a significant influence on employee performance through work discipline, while compensation directly does not. These results underscore the critical role of leadership and compensation in shaping work discipline and, ultimately, employee performance, offering valuable insights for organizational management and human resource practices. Highlights: Compensation and Leadership Influence: Both compensation and leadership play pivotal roles in shaping work discipline and employee performance. Work Discipline's Mediating Role: Work discipline acts as a significant intermediary in the relationship between leadership and employee performance. Practical Implications: These findings have practical implications for organizations aiming to enhance employee performance through effective compensation strategies and leadership practices. Keywords: Compensation, Leadership, Work Discipline, Employee Performance, Intervening Variable